Insights on the Use of Nanocarriers for Acne Alleviation - Amer, Sandra S.; Nasr, Maha; Mamdouh, Wael; Sammour, Omaima (Current Drug Delivery, 2019)
Among the common myths in the cosmetics industry is the perception that acne only happens to teenagers, and specifically to females. However, acne is neither limited to a specific age, nor to a certain gender, it creates a stressful problem for many people. Many chemical treatments for acne were proven to be successful, but when administered as such, they showed many adverse effects, starting from itching to skin dryness and inflammation. Natural remedies have also been explored for acne treatment, and despite their safety, they suffered many stability problems attributed to their physicochemical properties, creating an obstacle for their topical delivery. Therefore, many nanocarriers were used to deliver those chemical and natural remedies topically to maximize their therapeutic potential in acne treatment. The present review discusses the different nanocarriers which were proven successful in improving the acne lesions, focusing on vesicular, lipidic, and polymeric systems.
Keywords: inflammation